PENGARUH LOKASI, FASILITAS, DAN PELAYANAN TERHADAP KEPUASAN PENGUNJUNG DESA WISATA DAWUHAN, KEC. WANAYASA, KAB. BANJARNEGARA - Saputra, Andi Wahyu; ., Lustono; Suryani, Ratna (Medikonis, 2023)
Based on field data visitors to Dawuhan Tourism Village, Wanayasa District, Banjarnegara Regency are still complaining about incomplete and untidy facilities, the service and management system has not been maximized and is still chaotic and the arrangement of tourist attractions is not good and so that management services are considered less than optimal, in addition, the location is not strategic and difficult to access by visitors. This study aims to determine the influence of places, facilities and services on library visitor satisfaction in Dawuhan Tourism Village, Wanayasa District, Banjarnegara Regency. In this study using a field research approach (Field Research). Field Research is research conducted at the place of occurrence of symptoms using a type of quantitative research. The data collection methods used in this study were questionnaire (questionnaire) methods, and documentation. Before data analysis was carried out, validity and reliability tests were carried out on questionnaire questions. As for analyzing the data using quantitative analysis. After deepening research and data analysis resulted in the conclusion that the place variable has a positive and significant influence on visitor satisfaction, the level of significance is below 10% and df = 96, t value 2.661 > t table 1.658 and probability 0.009 < 0.100, Facility variables have a positive and quite significant influence on community satisfaction, significance levels of 10% and df 96, t values of 0.290 < t tables 1.658 and probability of 0.773 > 0.100, service variables have a positive and significant influence on visitor satisfaction, significance levels below 10% and df = 96, t values 5.716 t > table 1.658 and probability 0.000 < 0.100, the variables place, facilities and services together have a positive and significant influence on visitor satisfaction, with the results of calculating the significance of probability below 10% and df 96, amounting to 40.297 > f table 8.56 so that there is a simultaneous influence. The coefficient of determination is 0.557 (56%) which means that together it is influenced by the variables of place, facilities and services by 56%, while the remaining 44% is a dimension of other variables.